2023
DOI: 10.1200/po.23.00191
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Availability of Molecular Genotyping Results and Overall Survival in Patients With Advanced Nonsquamous Non–Small-Cell Lung Cancer

Abstract: PURPOSE Current guidelines recommend molecular genotyping for patients newly diagnosed with metastatic nonsquamous (mNSq) non–small-cell lung cancer (NSCLC). The association between availability of molecular genotyping before first line (1L) therapy and overall survival (OS) is not known. METHODS We conducted a real-world cohort study using electronic health records in patients newly diagnosed with mNSq NSCLC. Cox proportional-hazards multivariable regression models were constructed to examine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Molecular testing enables accurate identification of a specific tumor profile that indicates that a patient may be a candidate for targeted treatments that are more effective and less toxic. For patients, timely access to molecular testing leads to optimized personalized care that results in improved health outcomes, including clinical, quality of life, and survivorship outcomes [ 6 , 7 ], and by extension lower healthcare costs [ 8 ]. For clinicians, biomarker testing helps to predict and monitor response to therapies, increasing clinicians’ ability to prescribe or alter therapy at the right time for a patient to maximize treatment effectiveness, spare unnecessary treatments, and save healthcare resources [ 9 ].…”
Section: Why Is Timely Access To Molecular Testing Results An Imperat...mentioning
confidence: 99%
“…Molecular testing enables accurate identification of a specific tumor profile that indicates that a patient may be a candidate for targeted treatments that are more effective and less toxic. For patients, timely access to molecular testing leads to optimized personalized care that results in improved health outcomes, including clinical, quality of life, and survivorship outcomes [ 6 , 7 ], and by extension lower healthcare costs [ 8 ]. For clinicians, biomarker testing helps to predict and monitor response to therapies, increasing clinicians’ ability to prescribe or alter therapy at the right time for a patient to maximize treatment effectiveness, spare unnecessary treatments, and save healthcare resources [ 9 ].…”
Section: Why Is Timely Access To Molecular Testing Results An Imperat...mentioning
confidence: 99%
“…Patients with guideline-recommended molecular alteration-based therapies have better outcomes with first-line targeted therapy for advanced-stage NSCLC [ 1 ]. In a retrospective study, others showed a significant increase in OS in patients with non-squamous NSCLC with molecular testing available compared to non-tested patients [ 122 ]. Importantly, comprehensive NGS vs. incomplete or no testing before initiating first-line therapy impacts the OS (22.1 vs. 11.6 months, p = 0.017) respectively [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long TATs are often not compatible with the clinical conditions of cancer patients who might be referred to generic chemotherapy in the absence of biomarker information in clinically meaningful time frames. The implications stemming from extended TATs have been thoroughly examined in a pair of recent studies [ 19 , 20 ]. These investigations have delved into the effects of long TATs, particularly within the context of patients diagnosed with NSCLC.…”
Section: Discussionmentioning
confidence: 99%